Capital structure of Malaysian shariah-compliant firms - Thabet, Omer; Shawtari, Fekri Ali; Mohammed Ayedh, Abdullah; Ali, Fazlin (King Abdulaziz University Scientific Publishing Center, 2017)
This study examines the capital structure of choices in Sharīʿah-compliant markets in view of the numerous attempts made to address the issue of capital structure choice since 1958. None of these attempts studied the capital structure of Sharīʿah-compliant markets. This study applies the model proposed by Huang and Song (2006) to test the determinants of capital structure as suggested by capital structure theories. It uses the regression of fixed effect model to examine the relationship between capital structure and its determinants for 263 Sharīʿah-compliant firms listed on the Bursa Malaysia over the 2006-2011 period. The paper found evidence suggesting that the capital structure choice of Sharīʿah-compliant firms is influenced by factors such as non-debt tax shields (NDTS), profitability, and risks. However, there is no evidence of the influence of tax and tangibility on capital structure choice of Sharīʿah-compliant firms.